Urgency of Regulation of Business Judgment Rule As A Reason For Criminal Deletion In Criminal Acts of Corruption - Tohom Hasiholan; Abdul Madjid; Nurini Aprilianda; Adi Kusumaningrum (Faculty of Law, Merdeka University Surabaya, Indonesia, 2023)
State-Owned Enterprises are business entities whose capital is wholly or substantially owned by the state through direct participation originating from separated state assets. The Board of Directors is responsible for the business activities of the company as stipulated in Article 97 paragraph (1) of the Limited Liability Company Law, so that any decisions cannot be taken without taking into account the elements of prudence and applicable regulations. The purpose of establishing BUMN is to pursue profits, while in making decisions BUMN directors are often faced with decisions that are fraught with the risk of loss or bankruptcy so that a legal umbrella is needed for BUMN directors to relieve the responsibility borne by directors or what is known as the Business Judgment Rule. This study aims to determine the urgency of setting the Business Judgment Rule as a reason for eliminating criminal acts of corruption and this research uses juridical research methods. The research method uses normative juridical research with two approaches, namely the statute approach and case approach. Business decisions that are protected by the principles of the Business Judgment Rule are business decisions taken based on good faith and the principle of prudence. The existence of this principle will make the directors have no doubts in making business decisions because the principle of the Business Judgment Rule is an excuse if in the future there are things that must be accounted for by the directors.